El documento que emite la foto radar como medio de prueba en el esceso de velocidad fuera del rango moderado cometidas por los transportistas del gremio de taxis y su efécto jurídico en las contraversiones de tránsito, juzgadas en la Unidad Judicial Penal con sede en el cantón riobamba en el período de julio a diciembre del 2014. - Arguello Pérez, Luzkarime Rosa (2016)
This research discloses cause legal effect as the document issued photo radar as evidence in speeding the moderate range were committed by carriers Guild taxis in traffic violations, judged Unit Criminal court based in the canton Riobamba in the period from July to December 2014. The structure of this research is divided into five chapters: the first chapter deals with the frame of reference where the problem statement, originates its origin, as presented and how it behaves, after which formulated the general objective and specific objectives in order to determine the legal effect that causes document issued photo radar as evidence in speeding outside the moderate range committed by carriers Guild taxis in traffic violations, judged Criminal Judicial Unit based in the canton Riobamba in the period from July to December 2014, plus justification and importance of the problem where we note that this research work is feasible, innovative, original and serve for the general public. In the second chapter, the theoretical framework of signing the instrument through which doctrine, theories, concepts and bibliographic articles from books, laws, regulations and texts it comes to build the theoretical, conceptual part was obtained was applied develops, legal and doctrinal research, this chapter is divided into four units, with its subunits; in the first unit talk about crimes and violations ol Ira I fie, history, the criminal offenses Traffic offenses, both intentional crimes as malicious, speeding, traffic infringements according to COIP; in the second unit we will talk about speeding, speeding detected by photo radar, speeding in and out of speed limits, systems, equipment and control devices; in the third unit wiii talk about the evidence on speeding, the evidence, the test definition, legal evidence in general, the presentation of evidence, the burden of proof, in order to lest and legal base; in the fourth unit will talk about the legal effects of the radar picture on infringements for speeding outside the moderate range, the judgment confirms the innocence, the decision declaring guilt, deprivation of liberty point reduction in driver's license and finally the ease studies; in the filth unit we will talk about the legal effect that causes document issued photo  radar as evidence in speeding outside the moderate range committed by carriers taxi guild; the notional unit, hypotheses, v ariables, operationalization of variables. In the third chapter, we will develop the methodological framework, through the analytical method, we turn to the implementation of the research through research surveys applying to lawyers in free practice, in order to get to determine whether cause and effect the legal document issued photo radar as evidence in speeding outside the moderate range committed by carriers Guild taxis in traffic violations; and the application of interviews that a direct discussion with the judges of the Criminal Judicial Unit based in the canton Kiobamba, performing it with the entire population, the interview guide with inductive and analytical method was used; through the interview and the inductive method I could get the information that helped me somehow identify the legal effect that causes document issued photo radar as evidence in speeding outside the moderate range committed by carriers Guild tux is, on the other hand to apply the analytical method and reaching a critical legal analysis to verify the hypothesis. In the fourth chapter, the conclusions and recommendations obtained front research through interpretation and discussion of the results achieved in the statistical tables and charts, with the help of EXCEL software package in which results are obtained in exact percentages set for data processing, which is why this research is descriptive because after tabulate, interpret and process information, described the problem as it appears, behaving in its explanatory context the result after tabulated and calculated; Finally in the filth chapter the literature, supplementary literature, internet sources and Annexes.